Cohort study of malignancies and hospitalized infectious events in treated and untreated patients with psoriasis and a general population in the United States. (1st November 2015) - Kimball, A.B.; Schenfeld, J.; Accortt, N.A.; Anthony, M.S.; Rothman, K.J.; Pariser, D.
Summary: Background: Psoriasis is associated with risk of malignancy. Some psoriasis treatments may increase the risk of hospitalized infectious events (HIEs). Objectives: To evaluate rates of malignancies and HIEs in patients with psoriasis. Methods: This retrospective cohort study utilized data from MarketScan ® databases. Cohorts included adult general population (GP), patients with psoriasis, and patients with psoriasis treated with nonbiologics, adalimumab, etanercept, infliximab or phototherapy. Outcomes included incidence rates (IRs) per 10 000 person‐years observation (PYO) for all malignancies excluding nonmelanoma skin cancer (NMSC), lymphoma, NMSC, and per 10 000 person‐years of exposure (PYE) for HIEs. Results: Incidence rates [95% confidence interval (CI)] for all malignancies except NMSC were 129 (127–130) and 142 (135–149) for GP (PYO = 51 071 587) and psoriasis (PYO = 119 432) cohorts, respectively; 10·9 (10·5–11·3) and 12·9 (10·9–14·8) for lymphoma; and 145 (144–147) and 180 (173–188) for NMSC. Rates for all malignancies excluding NMSC were similar among treatments but variable for lymphoma and NMSC. IRs (95% CI) for HIEs were 332 (256–408) for the nonbiologic cohort (PYE = 3528); 288 (206–370) for etanercept (PYE = 6563); 325 (196–455) for adalimumab (PYE = 2772); 521 (278–765) for infliximab (PYE = 1058); and 334 (242–427) for phototherapy (PYE = 1797). IRs for HIEs were lowest for etanercept and higher in patients on baseline systemic corticosteroids across treatment cohorts. Conclusions: Malignancy rates were higher in patients with psoriasis than the GP, but these treatments did not appear to increase malignancy risk.